Extracellular Products of Streptococcus pyogenes and Their Involvement in Pathogenesis - Debbie Soefie Retnoningrum (Institut Teknologi Bandung, 2009)
Streptococcus pyogenes or group A streptococcus (GAS) is an exclusive human pathogen. To be a successful pathogen, this pathogen is equipped with various surface-exposed and secreted virulence factors. The functions of secreted virulence factors are particularly important since they interact with host components to establish infections and cause diseases in human. They include a number of proteases, DNase, superantigens, and plasminogen activator. How these secreted factors interact with host protein(s) define this pathogens ability to bring out various diseases. Several proteases act independently to target immunoglobulin molecules in order to evade host defense system and modulate host proteins to induce host-mediated damages. Besides producing proteases, many pathogenic strains of GAS also produce DNase; however, its involvement in host pathogenesis remains elusive. Superantigen, another secreted protein is responsive for serious host-destruction by bypassing antigen presentation to induce massive production of cytokines. GAS also secretes a plaminogen activator, streptokinase that is crucial for invasiveness. All together, secreted products of this pathogen work in concert to pinpoint different targets in order to destroy and or to disable human defense system and cause host damages.